2019
DOI: 10.1259/bjr.20180642
|View full text |Cite
|
Sign up to set email alerts
|

Imaging tumour hypoxia with oxygen-enhanced MRI and BOLD MRI

Abstract: Hypoxia occurs when the rate of oxygen delivery to tissue is inadequate to meet demand. 1 Disordered angiogenesis in tumours makes delivery inefficient, leading to hypoxia. This is a hallmark of cancer 2 and has been recognised for several decades as being a negative prognostic factor in most solid human cancers. 3-5 Furthermore, since the 1950s 6 hypoxia has been known to cause radioresistance, which results in failure in radiotherapy treatment. 7 More recently, tumour hypoxia has been implicated in the failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 94 publications
0
138
0
Order By: Relevance
“…However, the spatial resolution associated with PET imaging is low compared to the size of the hypoxic regions that can be found in tumor tissue [5]. Magnetic resonance imaging (MRI) techniques, including blood oxygen level dependent MRI (BOLD-MRI), tissue oxygen level dependent MRI (TOLD-MRI), oxygen-enhanced MRI (OE-MRI), and dynamic contrast-enhanced MRI (DCE-MRI), have also been applied to study tumor hypoxia [4,5,7,8]. MRI can be performed with substantially higher spatial resolution than PET imaging, and DCE-MRI is highly attractive because the technique is associated with a high signal to noise ratio and is routinely used to detect and characterize various types of cancer in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spatial resolution associated with PET imaging is low compared to the size of the hypoxic regions that can be found in tumor tissue [5]. Magnetic resonance imaging (MRI) techniques, including blood oxygen level dependent MRI (BOLD-MRI), tissue oxygen level dependent MRI (TOLD-MRI), oxygen-enhanced MRI (OE-MRI), and dynamic contrast-enhanced MRI (DCE-MRI), have also been applied to study tumor hypoxia [4,5,7,8]. MRI can be performed with substantially higher spatial resolution than PET imaging, and DCE-MRI is highly attractive because the technique is associated with a high signal to noise ratio and is routinely used to detect and characterize various types of cancer in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that when planning the combination therapy of radiation and evofosfamide, decreasing frequency of evofosfamide treatment may decrease the systemic toxicity without compromising the treatment effect. With methodologies to provide quantitative assessment of tumor oxygen with T1-weighted MRI on conventional clinical scanners implemented on human subjects 37,38 , such strategies will play a key role in tailoring therapies with evofosfamide and in combination with antiproliferative therapies such as conventional chemotherapy or radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In the body, oxygen affects MR contrast by acting as a paramagnetic relaxation agent thus shortening the T1 relaxation time, one of the principal sources of image contrast in MRI [18]. Perfused tumours contain a much higher concentration of oxygen than non-perfused tumours, and that oxygen causes a shortening in T1 relaxation in the tumour tissue [19][20][21]. The partial pressure of oxygen within the tumour cannot be determined from the T1 alone however.…”
Section: Introductionmentioning
confidence: 99%
“…One method of using this effect to infer perfusion levels is by inducing arterial hyperoxia to further shorten T1 of arterial blood and well-perfused tissues by breathing an increased inspired fraction of oxygen [18,22,23]. By acquiring a quantitative map of T1 values in each voxel (known as a ''T1 map") under normal conditions, and then performing the scan a second time while the patient is breathing an increased inspired fraction of oxygen via a face mask, the change in T1 between the air and oxygen T1 maps provides information about both the arterial blood volume in, and perfusion of the tumour [19]. It is by this mechanism that the changes in T1 from this oxygen-enhanced MRI could potentially differentiate perfused tumours from tumours with poor vascularity or hypoxia.…”
Section: Introductionmentioning
confidence: 99%